A walk around Bukhara - Tkacheva, Marina (project baikal, 2024)
The article describes a trip to Uzbekistan and, in particular, to Bukhara – the centre of medieval piety, scholarship, trade. It also features architectural sights of the city. The antiquity of the city is emphasized by numerous legends.
Keywords: Bukhara; madrasah; mosque; minaret; Shukhov Tower; Ark Fortress; Samanid dynasty